ANALISIS BIAYA PERSEMAIAN JELUTUNG RAWA (Dyera polyphylla (Miq.) Steenis) DI KALIMANTAN TENGAH - Jumri, Jumri; Mayawati, Sari (Lambung Mangkurat University Press, 2020)
The Analysis of cost and income for producing swamp jelutung seedlings (dyerapolyphylaa) by the Kahayan’s watershed management and protected forest center in Tumbang Nusa Central Borneo. This study aims to find out The cost analysis for producing seeds released by the Kahayan’s watershed management and protected forest center. The acceptance level analysis of the jelutung swamp plant business. The feasibility level analysis of the jelutung swamp plant business managed by watershed management center and protected forest. The relationship (correlation) analysis between the procurement of seeds carried out by the Kahayan’s watershed management and protected forest center and the welfare level of the receiving community. The data collections used the method of observation, interviews and notes. The data collection instruments used a questionnaire. The results of the cost analysis show that the total average costs of production spent is IDR 24,150,000. The income level of the swamp jelutung seedling business is 10,000 seedlings with an income of IDR 30,000,000. The analysis results showed that the Jelutung swamp seedling business was feasible to run, which was seen from the BCR value of 1.24 and has increased a profit with a BCR value of> 1. The results of the SPSS test with the Spearman’s test show that the coefficient of 0.986 criteria and the level of relationship strength are in the coefficient> 90. The level of relationship strength (the relationship is close to perfect).